2023
DOI: 10.1371/journal.pone.0286211
|View full text |Cite
|
Sign up to set email alerts
|

Elastin-targeted nanoparticles delivering doxycycline mitigate cytokine storm and reduce immune cell infiltration in LPS-mediated lung inflammation

Abstract: Background and purpose Cytokine storm invoked during acute and chronic lung injury promotes alveolar damage and remodeling. The current study shows that degraded elastin-targeted nanoparticles releasing doxycycline (Doxy NPs) are potent in mitigating cytokines storm, migration of immune cells in the lungs, and inhibiting inflammasome pathways in the LPS mouse model. Experimental approach Cytokine storm and lung injury were induced using LPS and elastase in C57BL/6 mice (rodent model for emphysema). The mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In addition to its antibacterial effect, it can also reduce systemic inflammation in patients with COPD ( 4 ). A recent study showed that doxycycline not only inhibits the activity of matrix metalloproteinases, but also suppresses immune cells and reduces cytokine storms ( 5 ). In a recent issue of the Journal , Allinson and colleagues reported a 12-month randomized controlled study ( 6 ) that enrolled patients with moderate to severe stable COPD and randomly assigned them to receive doxycycline (100 mg/d) or a placebo.…”
mentioning
confidence: 99%
“…In addition to its antibacterial effect, it can also reduce systemic inflammation in patients with COPD ( 4 ). A recent study showed that doxycycline not only inhibits the activity of matrix metalloproteinases, but also suppresses immune cells and reduces cytokine storms ( 5 ). In a recent issue of the Journal , Allinson and colleagues reported a 12-month randomized controlled study ( 6 ) that enrolled patients with moderate to severe stable COPD and randomly assigned them to receive doxycycline (100 mg/d) or a placebo.…”
mentioning
confidence: 99%